Using decomposition analysis to forecast metal usage in the building stock. Issue 1 (2nd January 2016) - Hatayama, Hiroki; Tahara, Kiyotaka
Abstract : As large amounts of materials are used and have accumulated in buildings and civil engineering projects, it is necessary to understand material flow in terms of construction sectors for resource management. The consumption, discard and in-use stock of four metals (steel, aluminium, copper and zinc) in Japan's building stock are forecast through to 2050. To clarify the factors that affect metal stocks and flows in construction, the metal consumption was decomposed into annual new floor area constructed and metal intensity ( i.e. the amount of metal used per unit floor area). The decomposition was meaningful for understanding characteristic patterns of factors of different metals and for envisaging future scenarios based on past trends. It was estimated that the annual new floor area constructed will remain at current levels, whereas metal intensity will have a significant impact on stocks and flows. The methodology developed in this study can be used to evaluate the impact of technology changes that would take place in building and civil engineering projects.